Implementasi Metode Extreme Progamming pada Aplikasi Food Market yang Sudah Terintegrasi dengan API dan Gateway Pembayaran Midtrans (Studi Kasus: Dad’s Bakery) - Faizal Alfarizi; Feri Agus Sianipar (CV. Multi Kreasi Media, 2025)
Along with the rapid growth of more and more technological developments and the convenience that people get in meeting their daily needs including their needs when transacting, almost 90% of people in Indonesia are more interested in making transactions from industry to technology-based finance, this allows users to make transactions anytime anywhere safely that has been provided and facilitated payments based on midtrans and payment gateways, Midtrans as a payment gateway service that offers payment solutions where most of its products are related to technical matters, making technical documentation one of the most important components in Midtrans. In the case of this research, the author conducted research at the Dad's Bakery shop which is engaged in the food sector which is a cake shop as well as a coffee shop that is still developing, which is located in BSD, South Tangerang City.